Design, synthesis and antimycobacterial activity of imidazo[1,5-a]quinolines and their zinc-complexes - Marner, Michael; Kulhanek, Niclas; Eichberg, Johanna; Hardes, Kornelia; Molin, Michael Dal; Rybniker, Jan; Kirchner, Michael; Schäberle, Till F.; Göttlich, Richard; Justus Liebig University Giessen (My University, 2024)
Tuberculosis has remained one of the world's deadliest infectious diseases. The complexity and numerous adverse effects of current treatment options as well as the emergence of multi-drug resistant M. tuberculosis (Mtb) demand research and innovation efforts to yield new anti-mycobacterial agents. In this study, we synthesized a series of imidazo[1,5-a]quinolines, including 4 new analogs, and evaluated their activity against Mtb. Inspired by previous studies, we also designed 8 compounds featuring a coordinated metal ion, determined their absolute configuration by single-crystal X-ray diffraction and included them in the bioactivity study. Remarkably, the metal complexation of 5c with either Zn2+ or Fe2+ increased the Mtb inhibitory activity of the compound 12.5-fold and reduced its cytotoxicity. Ultimately, out of the 21 analyzed imidazo[1,5-a]quinoline analogs, two zinc complexes (C1 and C7) showed the strongest, specific activity against Mtb H37Rv in vitro (IC90 = 7.7 and 17.7 μM).
Keywords: ddc:540